The given equation is
![x^2-4x+1=-3](https://img.qammunity.org/2023/formulas/mathematics/college/mg57l1cyn1n229p7v9gepjo0thh2qn4j2y.png)
First, we have to move the term -3
![\begin{gathered} x^2-4x+1+3=0 \\ x^2-4x+4=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/k00r8wurg9f29be091086srgx2l5t3wbob.png)
Where a = 1, b = -4, and c = 4.
The discriminant formula is
![D=b^2-4ac](https://img.qammunity.org/2023/formulas/mathematics/college/10i49byp4hi2dnkj3t3hcm4pmzk7llckdy.png)
Replacing the values, we have
![D=(-4)^2-4(1)(4)=16-16=0](https://img.qammunity.org/2023/formulas/mathematics/college/i8c4t1q37vhpbl8r343pcdbcozw4nxlicy.png)
The discriminant is zero.
Given that the discriminant is zero, it means the equation has a unique solution.